The Influence of Teacher’s Competence and Academic Supervision on Teacher’s Performance - Rahmadini, Miranda Ayu (PPSDP International Journal of Education, 2024)
Teacher’s competence is a set of mastery of knowledge, skills, and behaviors that teachers need to carry out their duties as educators and teachers to achieve educational goals. If a teacher is able to understand and master various competencies as an educator, he is considered a professional. Academic supervision is a supervisory activity that aims to improve the condition of educators and education personnel as well as other facilities that allow a better teaching and learning situation to achieve educational goals. Teacher’s competence and academic supervision are expected to affect teacher performance. This article uses a quantitative method that aims to analyze the influence of teacher’s competence and academic supervision partially and simultaneously on teacher performance at SMP Negeri 1 BP. Peliung. Hypothesis testing was carried out on partial variables through simple linear regression tests and on simultaneous variables through multiple linear regression tests. The results obtained showed that the partial influence was not significant with significance values of 0.745 and 0.526, respectively. This also applies to simultaneous variables, no significant influence was found with a significance value of 0.445.